The Revelation of Caput Succedaneum after Instrumental Assisted Deliveries: Exclusively diagnosed on Ultrasonography: Mini Article of Case Series - Siraj, Rabiya; Rehan, Rana; Shamim, Bushra; Rizwan, Bisma; Ali, Imtiaz; Khalid, Khubab (International Journal of Innovative Research in Medical Science, 2021)
Vacuum extraction delivery is one of the commonest and routinely available forms of assisted vaginal delivery in tertiary care hospitals. The association of caput succedaneum and mode of deliveries is sparsely discussed in any of the renowned platform. Here we are presenting case series of infants who presented to us with scalp swelling in our ultrasound suite and we diagnosed them as caput succedaneum exclusively on sonography with no need of CT or MRI scanning.